Genetic and hypoxic alterations of the microRNA‐210‐ISCU1/2 axis promote iron–sulfur deficiency and pulmonary hypertension. Issue 6 (30th March 2015) - White, Kevin; Lu, Yu; Annis, Sofia; Hale, Andrew E; Chau, B Nelson; Dahlman, James E; Hemann, Craig; Opotowsky, Alexander R; Vargas, Sara O; Rosas, Ivan; Perrella, Mark A; Osorio, Juan C; et al.
Abstract Iron–sulfur (Fe‐S) clusters are essential for mitochondrial metabolism, but their regulation in pulmonary hypertension (PH) remains enigmatic. We demonstrate that alterations of the miR‐210‐ISCU1/2 axis cause Fe‐S deficiencies in vivo and promote PH. In pulmonary vascular cells and particularly endothelium, hypoxic induction of miR‐210 and repression of the miR‐210 targets ISCU1/2 down‐regulated Fe‐S levels. In mouse and human vascular and endothelial tissue affected by PH, miR‐210 was elevated accompanied by decreased ISCU1/2 and Fe‐S integrity. In mice, miR‐210 repressed ISCU1/2 and promoted PH. Mice deficient in miR‐210, via genetic/pharmacologic means or via an endothelial‐specific manner, displayed increased ISCU1/2 and were resistant to Fe‐S‐dependent pathophenotypes and PH. Similar to hypoxia or miR‐210 overexpression, ISCU1/2 knockdown also promoted PH. Finally, cardiopulmonary exercise testing of a woman with homozygous ISCU mutations revealed exercise‐induced pulmonary vascular dysfunction. Thus, driven by acquired (hypoxia) or genetic causes, the miR‐210‐ISCU1/2 regulatory axis is a pathogenic lynchpin causing Fe‐S deficiency and PH. These findings carry broad translational implications for defining the metabolic origins of PH and potentially other metabolic diseases sharing similar underpinnings.